Gharīb ul Ḥadīth According to Imam al-Humaydi in His Musnad - Darash, Abd al Razzaq Hasan (Journal of Islamic and Religious Studies, 2025)
The research dealt with an essential topic in hadith sciences, specifically the science of strange hadith, as outlined by Imam al-Hamidi in his Musnad. By a peculiar hadith, he means ambiguous words that are far from understanding due to their lack of use. It is one of the arts that the hadith scholars paid attention to, so they devoted it to special works and compilations that are well-known and famous, and Imam al-Hamidi had a role in that. In the folds of his Musnad, Imam Al-Humaidi had an approach to this. Sometimes he would explain the hadith on his initiative, sometimes he would transmit it from his teacher Sufyan bin Uyaynah, and sometimes he would transmit it from his teacher’s teacher, Al-Zuhri. Imam Al-Humaidi agreed with other imams regarding the explanation of the strange hadith. The research was divided into two basic sections: the first section was the introduction by the Imam. Al-Hamidi and his Musnad, and the second: examining the places in which Gharib explained the hadith in his Musnad. The study followed the inductive approach in introducing Imam Al-Hamidi and his explanation of the strange hadith in his Musnad, and the analytical approach in studying his explanation of the peculiar hadith and comparing his statement with the statement of other imams.